Links between MIS 11 millennial to sub-millennial climate variability and long term trends as revealed by new high resolution EPICA Dome C deuterium data – A comparison with the Holocene. - Pol K.; Debret M.; Masson Delmotte V.; Capron E.; Cattani O.; Dreyfus G.; Falourd S.; Johnsen S.; Jouzel J.; Landais A.; Minster B.; STENNI, BARBARA (Climate of the Past, 2011)
We expand here the description of the Antarctic temperature variability during the long interglacial period occurring about 400 thousand years before the present (Marine Isotopic Stage, MIS 11). Our study is based on new detailed deuterium measurements conducted on the EPICA Dome C ice core, Antarctica, with about 50 year temporal resolution. Despite an ice diffusion of a length reaching about 8 cm at MIS11 depth, the data allow us to highlight a variability at multicentennial scale for MIS 11, as it has already been observed for the Holocene period (MIS 1). The differences between MIS 1 and MIS 11 are analysed regarding the links between multi-millennial trends and sub-millennial variability. The EPICA Dome C deuterium record shows an increased variability and the onset of millennial to sub-millennial periodicities at the beginning of the final cooling phase of MIS 11. Our findings are robust with respect to sensitivity tests on the somewhat uncertain MIS 11 duration.